Preliminary analysis on generated jet pressure from ionic polymer composite actuated radial contraction using balloon manometry technique - S., Muhammad Farid; Z., Samad; A.B., Husaini; M.R., Arshad; S., Mahzan (National Institute of Science Communication And Information Resources, 2013)
Contractile thruster has become a trend for underwater robot propulsion because of its prospective and advantages. However, it is difficult to determine the performance of the generated jet pressure from the small thruster. Thus, in this research an analysis was carried out to observe the radial contraction effects on the jet pressure by applying balloon-manometry technique. Four Ionic Polymer-Metal Composite (IPMC) filament actuators had been utilized as the longitudinal artificial muscle. The lengths of the IPMC actuators were 30 mm, 40 mm and 50 mm. During actuation, the radial contraction differentiated the pressure in the cylindrical shape balloon which was measured by a gauge pressure transducer. The result shows that at 30 mm length, the obtained pressure was almost 0.01psi. The shorter IPMC actuator gave higher contraction force and propulsive pressure.